Vascular flora changes in canopy gaps caused by wind - Kurek, Przemysław; Wiatrowska, Blanka; Tyburski, Łukasz; Marczak, Dawid (Biodiversity: Research and Conservation, 2022)
A study on the importance of wind-induced canopy gaps was conducted in Kampinos National Park (Poland) between2018 and 2021. Two types of habitats were considered – dry mesotrophic oak forest and wet Scots pine forest (Molinio- Pinetum). Canopy gaps were characterized by higher plant species richness than in adjacent areas, and their effect was weaker in oligotrophic coniferous forest than in mesotrophic deciduous oak stand.